Healthcare costs of a telemonitoring programme for heart failure: indirect deterministic data linkage analysis. (10th August 2022) - Pathak, Atul; Levy, Pierre; Roubille, François; Chatellier, Gilles; Mercier, Grégoire; Alami, Sarah; Lancman, Guila; Pasche, Hélène; Laurelli, Corinne; Delval, Cécile; Ramirez‐Gil, Juan Fernando; Galinier, Michel
Abstract: Aims: We aim to evaluate the costs associated with healthcare resource consumption for chronic heart failure (HF) management in patients allocated to telemonitoring versus standard of care (SC). Methods and results: OSICAT‐ECO involved 745 patients from the OSICAT trial (NCT02068118) who were successfully linked to the French national healthcare database through an indirect deterministic data linkage approach. OSICAT compared a telemonitoring programme with SC follow‐up in adults hospitalized for acute HF ≤ 12 months. Healthcare resource costs included those related to hospital and ambulatory expenditure for HF and were restricted to direct costs determined from the French health data system over 18 months of follow‐up. Most of the total costs (69.4%) were due to hospitalization for HF decompensation, followed by ambulatory nursing fees (11.8%). During 18‐month follow‐up, total costs were 2% lower in the telemonitoring versus the SC group, due primarily to a 21% reduction in nurse fees. Among patients with NYHA class III/IV, a 15% reduction in total costs (€3131 decrease) was observed over 18‐month follow‐up in the telemonitoring versus the SC group, with the highest difference in hospital expenditure during the first 6 months, followed by a shift in costs from hospital to ambulatory at 12 months. Conclusions: HF hospitalization and ambulatory nursing fees represented most of the costs related to HF. No benefit was observed for telemonitoring versus SC with regard to cost reductions over 18 months. Patients with severe HF showed a non‐significant 15% reduction in costs, largely related to hospitalization for HF decompensation, nurse fees, and medical transport.